“The last journey of the heart”: the myth of Ivan Turgenev in the story “The Revival” by Julian Barnes - Анненкова, Елена (Slavia Centralis, 2023)
The article deals with the short story “The Revival”, by English writer Julian Barnes, as updating the biographical myth about Russian writer Ivan Turgenev. The author highlights the key mythologems that mark the Russian writer’s image and help to model the English postmodern version of the myth about Turgenev. There are such mythologems as unrealised love and Turgenev’s inherent fear of life and lack of will to act. In the work, particular attention is paid to artistic techniques through which the image of Turgenev is embodied, and the motives of Barnes’ appeal to the personality of the Russian writer are traced; aspects of creative rapprochement and ideological consonances of writers of different eras, cultures and nationalities are analysed. As a result, the hypothesis about the closeness and consonance of the artistic consciousness of English and Russian writers is confirmed.
Keywords: Julian Barnes; Ivan Turgenev; myth; biographical myth; cultural hero; love